Differential diagnostics and special specific prophylaxis of tick-borne infections in Irkutsk city - I. V. Kozlova; V. I. Zlobin; M. M. Verkhozina; M. A. Khasnatinov (Бюллетень сибирской медицины)
The results of differential express diagnostic of tick-borne encephalitis and Lyme borreliosis agents in ticks, removed from pa- tients are present in this article (1995—2004). The entire complex of serolological and genetical methods were used. The specific prophylaxis based on the results of diagnostic had shown to be very effective for both infections. The first data about human ehrli- chiosis and anaplasmosis in Irkutsk region had been obtained. The improvement of diagnostic and prophylactic procedures are pro- posed.